(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
This article engages with Wole Soyinka’s parody on the current postcolonial realities Alapata Apata (2011). The article begins by isolating, at least, two major dimensions discernible in Soyinka’s dramaturgy- in the nodes of cultural revalidation and social interventions- and their links with Ogun in Soyinka’s plays. The paper brings these into relation with the diverse social phases and crises mirrored in Soyinka’s plays and narrows down to the current post dictatorship phase where, like other interventions Soyinka presented an avatar of Ogun in his interrogation of leadership failure and other social malaises. The paper argues that the playwright’s re-invention of Ogun is a radical departure from the avant-gardist disposition of all other Ogun avatars that preceded Alaba. The conclusion of the paper, on account of Alaba’s accidental canoniszation, is interpreted as Soyinka’s veiled chastisement of political leaders whose failures have perpetuated diverse crises in the space mirrored in the play.